Disability and visual outcomes following suspected abusive head trauma in children under 2 years - Wright, J; Painter, S; Kodagali, S; Jones, N; Roalfe, A; Jayawant, S; Elston, J; Anand, G (BMJ Publishing Group, 2020)
Aim To report disability and visual outcomes following suspected abusive head trauma (AHT) in children under 2 years.